THE EFFECTIVENESS OF AI-BASED Grammarly FOR LEARNING ENGLISH GRAMMAR IN HIGHER EDUCATION - Endang Trirezeki; Ilham; Irwandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study investigates the effectiveness of AI-based Grammarly in improving English grammar learning among higher education students. A quantitative quasi-experimental design was employed involving two groups of undergraduate students: semester 3 students (n = 24) and semester 5 students (n = 28). Both groups were given a grammar pre-test, followed by instructional treatment using Grammarly, and a post-test after the intervention. The data were analyzed using descriptive statistics and paired sample t-tests. The results indicate that Grammarly significantly improved students’ grammar performance in both groups. These findings suggest that AI-based writing tools can be an effective supplementary resource for grammar learning in higher education. Keywords: Grammarly, artificial intelligence, grammar learning, higher education